Ethology as a Collaborative Factor for the Reduction of Complaints of Family Violence due to Physical Aggression in Peru (LACCEI, 2024)
Abstract— The new concept of Evolution Coefficient (E) in Peru examines the levels of Complaints of Family Violence due to Physical Aggression (DVFAF), both dimensions of Ethological Factors'. The levels of the variables of the Collaboration Factors' grouped into three dimensions are also examined: Social, Economic and Human Resources in Education and Health in the 24 Departments of Peru. The dataset © of the National Institute of Statistics (INEI) between 2010 and 2020 is used. Economic inactivity (men and women) and GDP as economic concepts added to the participation of professors and collegiate doctors as human resources available in each territory, destined to calculate patterns of family violence in the national geographic diversity. The E Coefficient maintains a strong correlation with the dimensions of the Collaboration Factors' (R2=0.99 F(11,247) = 2,479.73 p 001), which makes it possible to visualize the levels of family violence. A strong correlation is identified between the E Coefficient and DVFAF (R2=0.91 F(1,262) = 2,478.19 p 001), which corroborates the link between DVFAF dimension and Collaboration Factors' in Peru. In the case of economically active men, 31.88 cases of DVFAF are reduced (R2=0.91 F(1,286) = 2,951.79 p 001). In 2020, 75% of Peru is at least 4 times more violent than in 2010. The value of Eta square, indicated a large effect of the Departments on the E coefficient (F(23,240) = 3.20 p 001, η2 = 0.23). It is recommended to account for the job opportunities of citizens, as well as to train Health and Education professionals around social problems, taking into account the need for a multidisciplinary perspective to reduce family violence in Peru.